Investigating the antioxidant activity enhancer effect of Cyamopsis tetragonoloba seed extract on phenolic phytochemicals - Joshi, Tripti; Mandal, Sumit Kumar; Puri, Sonakshi; Asati, Vidushi; Deepa, P. R.; Sharma, Pankaj Kumar (Frontiers in Plant Science, 2023)
Phenolic phytochemicals are known for antioxidant-mediated pharmacological effects in various diseases (diabetes, cancer, CVDs, obesity, inflammatory and neurodegenerative disorders). However, individual compounds may not exert the same biological potency as in combination with other phytochemicals. Cyamopsis tetragonoloba (Guar), an underutilized semi-arid legume which has been used as a traditional food in Rajasthan (India), is also a source of the important industrial product guar gum. However, studies on its biological activity, like antioxidant, are limited. Here, we tested the effect of C. tetragonoloba seed extract to enhance the antioxidant activity of well-known dietary flavonoids (quercetin, kaempferol, luteolin, myricetin, and catechin) and non-flavonoid phenolics (caffeic acid, ellagic acid, taxifolin, epigallocatechin gallate (EGCG), and chlorogenic acid) using DPPH radical scavenging assay. In most cases, we observed synergy at lower concentrations of the seed extract (0.5-1 mg/ml). The extract concentration of 0.5 mg/ml enhanced the antioxidant activity of Epigallocatechin gallate (20 µg/ml) by 2.07-folds, implicating its potential to act as an antioxidant activity enhancer. This synergistic seed extract-EGCG combination was further validated for its cytoprotective and anti-lipid peroxidative effects in in vitro cell culture system, at different concentrations of the extract. LC-MS analysis of the purified guar extract revealed some previously unreported metabolites, including catechin hydrate, myricetin-3-galactoside, gossypetin-8-glucoside, and puerarin (daidzein-8-C-glucoside) which possibly explains its antioxidant enhancer effect. The outcomes of this study could be used for development of effective nutraceutical/dietary supplements.